2017
DOI: 10.1257/jep.31.4.73
|View full text |Cite
|
Sign up to set email alerts
|

From Proof of Concept to Scalable Policies: Challenges and Solutions, with an Application

Abstract: The promise of randomized controlled trials is that evidence gathered through the evaluation of a specific program helps us—possibly after several rounds of fine-tuning and multiple replications in different contexts—to inform policy. However, critics have pointed out that a potential constraint in this agenda is that results from small “proof-of-concept” studies run by nongovernment organizations may not apply to policies that can be implemented by governments on a large scale. After discussing the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
62
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 230 publications
(100 citation statements)
references
References 45 publications
3
62
0
6
Order By: Relevance
“…Moreover, risk averse individuals might be less likely to enroll in an experiment (Al‐Ubaydli and List ; Heckman ). Participation bias may also arise in the field, because organizations who agree to collaborate with researchers in an experiment are usually exceptional (Banerjee et al ). Consider the example of Behaghel, Crépon, and Barbanchon (), where French firms could opt into an experiment that randomly anonymized the resumes they received from job applicants.…”
Section: Dozen Thingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, risk averse individuals might be less likely to enroll in an experiment (Al‐Ubaydli and List ; Heckman ). Participation bias may also arise in the field, because organizations who agree to collaborate with researchers in an experiment are usually exceptional (Banerjee et al ). Consider the example of Behaghel, Crépon, and Barbanchon (), where French firms could opt into an experiment that randomly anonymized the resumes they received from job applicants.…”
Section: Dozen Thingsmentioning
confidence: 99%
“…Moreover, program evaluations are often run by particularly high‐quality officials or NGOs in a way that is hardly possible to scale up: as the program is expanded, its quality may deteriorate (Duflo, Glennerster, and Kremer ). When scaling, researchers need to be aware that more workers must be hired, and they might be of lower quality or have less interest in the program, simply due to the diseconomies of scale associated with requiring more labor in a labor market with inelastically supplied human capital (Al‐Ubaydli, List, and Suskind ; Davis et al ; Banerjee et al ). This may reduce the benefits of the program (through lower‐quality program workers) and/or increase its costs (when trying to keep the quality of workers high).…”
Section: Dozen Thingsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies in the global evidence base have shown that when smaller-scale programs go to a larger scale, positive effects are often diminished or lost (for example, Bold, Kimenyi, Mwabu, Ng'ang'a, & Sandefur, 2013;Dodge, 2011). On the other hand, some recent examples show success when the process of scaling involves multiple stages and testing in a variety of local policy and implementation contexts-that is, when across iterations the core of a program's active ingredients are maintained in adaptations to larger systems-level factors, such as workforce capacity, local policy, supervision and governance (Banerjee et al, 2016). "Small to bigger" expansion may be more successful if planning for scale occurs starting during the phase of small-scale implementation (Dodge, 2011;Supplee & Metz, 2015).…”
mentioning
confidence: 99%